Analisis Psikologi Tokoh dalam Naskah Drama Pinangan Karya Anton P. Chekhov Saduran Jim Lim Suyatna Anirun dengan Pendekatan Psikologi Analitis Carl Gustav Jung serta Implikasinya Terhadap Pembelajaran - Wildan Fauzi Mubarock (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, UNPAK, 2021)
Literary works are very broad, and drama scripts are included. In general the drama script raised about the story of human life. The story of human life is played beautifully by each character. Each character has their own psychology which describes the personality structure that exists in him. This paper will examine the characters in the drama script Pinangan by Anton P. Chekhov adaptation of Jim Lim Suyatna Anirun based on aspects of Carl Gustav Jung's Analytical Psychology. The focus of this research is to analyze the psychology of the main character in the script play Pinangan by Anton P. Chekhov adaptation of Jim Lim Suyatna Anirun with Carl Gustaf Jung's Analytical Psychological approach and its implications for learning Indonesian in high school. The purpose of this study is to determine the psychology that exists in the main character and its implications in learning Indonesian. This shows that the conflict in the story presented in the drama script is about love and debate, and no one wants to reduce their egos in dealing with every problem that comes. Thus, it can be concluded that the main character of the drama script Pinangan is a person who has a personality structure according to Carl Gustav Jung's Analytical Psychological theory. The implications of the Pinangan drama script in Indonesian language learning are contained in the basic competencies of 3.18 and 4.18 2013 curriculum which emphasizes that students can show one of the characters in a drama that is read or watched orally in a literary work, this is in accordance with the personality of the main character that is very unique and interesting for students to play and to hone the acting talent in students.